Różewicz: White Scarves of Childhood - Andrzej Skrendo (Jagiellonian University Press, 2024)
Tadeusz Różewicz had created the myth of childhood in his work, especially in later years. This myth is based on several assumptions. First, that a poet is someone who has a special relationship with his mother throughout his life (the poet's mother was a Jewish convert to Catholicism). Second, that childhood is a source to which one must return in order for poetry to exist in a world that no longer has values after the war and the Holocaust. Third, that childhood is a time of innocence in which one cannot distinguish between good and evil. In contrast to these assumptions, the author of the article argues that - first of all - the relationship with the mother has the other side, namely the relationship between father and son. Różewicz enters it as a son and as a father of his own two sons. Second, that there is no return to childhood, it is above the order of time, and this space above time is not the order of myth, but of trauma. Thirdly, Różewicz's childhood is internally marked by the experience of evil - childhood is not innocent.